2018
DOI: 10.7717/peerj.5170
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of triclosan resistance in Vibrionaceae

Abstract: The antimicrobial additive triclosan has been used in personal care products widely across the globe for decades. Triclosan resistance has been noted among Vibrio spp., but reports have been anecdotal and the extent of phenotypic triclosan resistance across the Vibrionaceae family has not been established. Here, triclosan resistance was determined for Vibrionaceae strains across nine distinct clades. Minimum inhibitory concentrations (MIC) were determined for 70 isolates from clinical (n = 6) and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Based on the reported values given in Table 1 , TCS concentrations in surface water were several times higher than the predicted no observed effect concentration (PNEC) of TCS set by European Commission (0.069 nM). Hence, the current prioritization methodology of TCS is questionable due to the growing resistance of the vast groups of bacteria and the demonstrated TCS toxicity toward different aquatic organisms at the environmental levels (Khatikarn et al 2018 ; Lydon et al 2018 ; Westfall et al 2019 ).…”
Section: Occurrence Of Tcs In Different Environmental Matricesmentioning
confidence: 99%
“…Based on the reported values given in Table 1 , TCS concentrations in surface water were several times higher than the predicted no observed effect concentration (PNEC) of TCS set by European Commission (0.069 nM). Hence, the current prioritization methodology of TCS is questionable due to the growing resistance of the vast groups of bacteria and the demonstrated TCS toxicity toward different aquatic organisms at the environmental levels (Khatikarn et al 2018 ; Lydon et al 2018 ; Westfall et al 2019 ).…”
Section: Occurrence Of Tcs In Different Environmental Matricesmentioning
confidence: 99%
“…In August 2014, a sucrose fermentation-positive presumptive Vibrio isolate (strain DA9) was isolated from surface seawater in a coastal canal (24.700389, –81.352000) in the Florida Keys (USA) after growth on thiosulfate-citrate-bile salts-sucrose (TCBS) agar plates at 30°C overnight ( 9 ). Further characterization of strain DA9 through hsp60 sequencing ( 10 ) revealed that it was closely related to V. vulnificus (84.6% nucleotide identity) and subjected to further investigation through antibiotic resistance screening and whole-genome sequencing.…”
Section: Announcementmentioning
confidence: 99%